ASSESSMENT OF TIME IN THERAPEUTIC RANGE WITH WARFARIN THERAPY IN PHARMACIST VERSUS USUAL CARE GROUP: A RETROSPECTIVE COHORT STUDY - MAJERCZYK, DANIEL; RUSCHE, KIMBERLY; SAKHARKAR, PRASHANT (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Anticoagulation management with warfarin is a familiar challenge seen in primary care settings. A greater time in the therapeutic range (TTR) has shown improved health benefits in patients treated with warfarin for atrial fibrillation. The aim of this study was to assess the level of anticoagulation control achieved with warfarin therapy measured by TTR. Methods: Patients attending anticoagulation service at a medical center were included in this retrospective cohort study. Patients with at least two international normalized ratio (INR) values not more than 4 weeks apart were included and placed in a usual care group or a pharmacist care group based on the care received. Anticoagulation control was measured by calculating TTR according to Roosendaal’s linear interpolation method. A TTR of >70% was considered high-quality and >60% was considered moderate coagulation control. The data were analyzed for descriptive statistics, associations, and for identifying predictors of TTR. A p value of <0.05 was considered statistically significant. Results: Mean age of patients was 58±9 years; 57% were male; 48% were White Caucasian, and 43% had a CHADS2 score of ≥3. Patients in the pharmacist group had a high TTR (67.6% vs. 43.4%, p<0.0001) and an INR in a significantly lower sub-therapeutic range than the usual care group (5.6% vs. 14.8%; p<0.0001). Half of the patients in the pharmacist group were able to achieve a TTR threshold of 60% and greater compared to less than one-third among the usual care group. Age and pharmacist care were found to be great predictors of TTR after adjusting for gender, ethnicity, and CHADS2 score (p<0.001). Conclusion: Our findings confirmed that pharmacist led anticoagulation care positively improved patients’ TTR with warfarin.